More Than Meets the Eye: Art Engages the Social Brain - van Leeuwen, Janneke E. P.; Boomgaard, Jeroen; Bzdok, Danilo; Crutch, Sebastian J.; Warren, Jason D. (Frontiers in Neuroscience, 2022)
Here we present the viewpoint that art essentially engages the social brain, by demonstrating how art processing maps onto the social brain connectome — the most comprehensive diagram of the neural dynamics that regulate human social cognition to date. We start with a brief history of the rise of neuroaesthetics as the scientific study of art perception and appreciation, in relation to developments in contemporary art practice and theory during the same period. Building further on a growing awareness of the importance of social context in art production and appreciation, we then set out how art engages the social brain and outline candidate components of the ‘artistic brain connectome’. We explain how our functional model for art as a social brain phenomenon may operate when engaging with artworks. We call for closer collaborations between the burgeoning field of neuroaesthetics and arts professionals, cultural institutions and diverse audiences in order to fully delineate and contextualise this model. Complementary to the unquestionable value of art for art’s sake, we argue that its neural grounding in the social brain raises important practical implications for mental health, and the care of people living with dementia and other neurological conditions.